Pengaruh modernisasi sistem administrasi perpajakan, pengeahuan wajib pajak dan sanksi perpajakan terhadap kepatuhan wajib pajak UMKM dengan sosialisasi perpajakan sebagai variabel modernisasi - Iin Nur Ainiyah; Eka Febriani (Jurnal Ilmiah Bisnis dan Perpajakan (Bijak), 2023)
This study aims to determine the effect of modernization of the tax administration system, taxpayer knowledge and tax sanctions on MSME taxpayer compliance and the role of tax socialization as a moderating variable. The number of samples used in this study were 100 respondents. The analysis tool used was PLS-SEM with the SmartPLS version 4 program. The results showed that modernization of the tax administration system, taxpayer knowledge and tax sanctions had a positive and significant effect on taxpayer compliance. Tax socialization plays a role in moderating the effect of taxpayer knowledge on taxpayer compliance; tax socialization does not play a role in moderating the influence of modernization of the tax administration system and tax sanctions on taxpayer compliance.